2021
DOI: 10.3390/ijerph18126296
|View full text |Cite
|
Sign up to set email alerts
|

Preventive Effects of Sustainable and Developmental Perioperative Oral Management Using the “Oral Triage” System on Postoperative Pneumonia after Cancer Surgery

Abstract: Perioperative oral management is widely recognized in the healthcare system of Japan. Conventionally, the surgeon refers patients with oral problems to a dental or oral surgery clinic in the hospital. However, frequent in-house referrals were found to increase the number of incoming patients resulting in unsustainable situations due to an insufficient workforce. In 2011, the Center for Perioperative Medicine was established at our hospital to function as a management gateway for patients scheduled to undergo s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 16 publications
1
15
0
1
Order By: Relevance
“…In addition, we found that the older patients needed more extensive oral management. These results are supported by past reports that older people have more oral troubles [14] and are at a greater risk of the onset of postoperative pneumonia [11].…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…In addition, we found that the older patients needed more extensive oral management. These results are supported by past reports that older people have more oral troubles [14] and are at a greater risk of the onset of postoperative pneumonia [11].…”
Section: Discussionsupporting
confidence: 88%
“…There have been only a few studies on preoperative oral screening. For instance, Sekiya et al [11] evaluated nine categories (i.e., teeth movement, gingiva inflammation, dental calculus, dental plaque, tongue, xerostomia, halitosis, dysphagia, and trismus) and recommended patients to visit an oral surgery clinic if there was even one problematic finding. As a result, the number of patients who underwent oral screening and required oral management was found to range from 16.4% to 26.5%.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, the protocol for the technique of perioperative oral management has not been standardized at the eight institutions. However, according to Sekiya et al [ 10 ], this management method is positioned as a conventional system in the Japanese classification of perioperative oral management systems. In other words, this is a system in which professional oral management is performed only when the surgeon in charge requests oral management before the operation.…”
Section: Introductionmentioning
confidence: 99%